Forecasting prevalence of dengue hemorrhagic fever using ARIMA model in Sulawesi Tenggara Province, Indonesia - Mistawati, Mistawati; Yasnani, Yasnani; Lestari, Hariati (Public Health of Indonesia, 2021)
Background: Dengue hemorrhagic fever occurs through the bite of Aedes mosquitoes, primarily Aedes aegypti, carrying dengue viruses. In recent decades, the risk increased dramatically, not only in the tropics but also in subtropical regions.Objective: This study aimed to determine the best model for forecasting dengue hemorrhagic fever prevalence in Sulawesi Tenggara, Indonesia.Method: This was a retrospective analytical study using secondary data from the Sulawesi Tenggara Provincial Health Office from 2014 to 2019. ARIMA model was used for data analysis.Results: ARIMA (0.1.1)(0.1.1)4 was selected as the best-suited model. Based on the forecast, there would be an increase in dengue hemorrhagic fever prevalence over the next two years, with a mean absolute percentage error value of 4.41%.Conclusion: Forecasting results indicated that the peaks of dengue hemorrhagic fever cases would be in March, July, and November, and the increase will occur in the same months each year. Also, forecasting results were very good. Public health practitioners can use this model to prevent and eradicate dengue hemorrhagic fever. The ARIMA model would also be useful for nursing practice in caring for patients with dengue fever in the future.